Larangan dan Hukum Mengkonsumsi Hewan Buruan yang Bertaring dalam Perspektif Hadis - Fitria Fitria (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about game animals. This study uses a qualitative approach by applying the descriptive-analytical method. The object of this research format is the science of hadith, while the material object is the hadith about game animals in the history of Ibn Majah No. 3225. The results and discussion show that the status of the hadith is authentic li ghairihi that meets the maqbul ma'mul bih qualifications for Islamic observation. This study concludes that the hadith narrated by Ibn Majah no. 3225 is relevant to be used as a law, prohibition, and direction for Muslims to be careful in consuming food, especially game animals.